If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1277 = 4r * 3 Reorder the terms for easier multiplication: 1277 = 4 * 3r Multiply 4 * 3 1277 = 12r Solving 1277 = 12r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-12r' to each side of the equation. 1277 + -12r = 12r + -12r Combine like terms: 12r + -12r = 0 1277 + -12r = 0 Add '-1277' to each side of the equation. 1277 + -1277 + -12r = 0 + -1277 Combine like terms: 1277 + -1277 = 0 0 + -12r = 0 + -1277 -12r = 0 + -1277 Combine like terms: 0 + -1277 = -1277 -12r = -1277 Divide each side by '-12'. r = 106.4166667 Simplifying r = 106.4166667
| y(y)-y=0 | | y=180+45x | | -8(5-5k)=-40-6k | | y+y=1 | | -8(5-5x)=-40-6x | | -(k-8)-7=-11+5k | | 124/6+44=h | | (4+w)(5w+6)=0 | | 7a+11=3a+21 | | 4c^3+4c^2-80c=0 | | 7x+22=9(x-4) | | 56/11 | | 2(5n+8)=-16+6n | | x+3=6(8-3x)-7 | | 7150=6.25*r*5 | | A=1/2*bh | | 5x+3y=40 | | -6a+28=-(2a-8) | | 9x^2+18x+17=0 | | 5c^3+30c-35c=0 | | 3(-8n-2)=-2n+16 | | 24x-4x^2=0 | | 3y-9=6y+3 | | 5x+5(2+6x)=10+3x | | (6+y)(3y+7)=0 | | (2x)lnx+x=0 | | -15-5r=5(1+3r) | | (5v-7)(3-v)=0 | | 4x+4=5x+10 | | (2n-3)(n+4)=0 | | 6c-6-2c-5-3c+7= | | 8+(x+5)= |